2012
DOI: 10.5424/sjar/2012103-564-11
|View full text |Cite
|
Sign up to set email alerts
|

El control de las emisiones de gases de efecto invernadero en España: costes para los sectores agrarios

Abstract: Employing a recursive dynamic computable general equilibrium (CGE) model of the Spanish economy, this study explicitly aims to characterise the potential impact of Kyoto and European Union environmental policy targets on specific agricultural activities up to 2020. The model code is modified to characterise the emissions trading scheme (ETS), emissions quotas and carbon taxes, whilst emissions reductions are applied to all six registered greenhouse gases (GHGs). Compared to a 'business-as-usual' baseline scena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…For instance, in Spain, the agricultural sector contributes 14% of the country's total greenhouse gas (GHG) emissions (Bourne et al, 2012). Hedenus et al (2014) showed that emission reduction in the agro-food sector can be achieved by: 1) productivity improvements; 2) technological changes (supply-side measures); and 3) changes in consumption behaviour (demand-side measures).…”
Section: Consumption Introductionmentioning
confidence: 99%
“…For instance, in Spain, the agricultural sector contributes 14% of the country's total greenhouse gas (GHG) emissions (Bourne et al, 2012). Hedenus et al (2014) showed that emission reduction in the agro-food sector can be achieved by: 1) productivity improvements; 2) technological changes (supply-side measures); and 3) changes in consumption behaviour (demand-side measures).…”
Section: Consumption Introductionmentioning
confidence: 99%
“…Chalak et al (2008) analyzed the impact of a pesticide tax on agricultural production and found that it can effectively reduce pesticide usage, leading to improvements in environmental governance and consumer health. Bourne et al (2012) studied the effects of various environmental regulations on agricultural CO 2 emissions in Spain and found that taxation could result in a decrease in agricultural production, an increase in agri-food prices, and a decline in farmers' income. Meng (2015) analyzed the introduction of a carbon tax in the Australian agricultural sector and found that while it significantly reduces emissions, the cost of the tax can spread to other sectors of the economy, resulting in reduced production, employment, and earnings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, some international studies have found that carbon abatement policies (e.g. carbon tax) led to the decreases in agricultural productions and consumptions as well as an increase in the price level of agricultural products and worsened farmers' income and welfare (Bourne et al, 2012;Moberg et al, 2021;Gren et al, 2021). Whereas, other studies have found that carbon abatement policies may do harm to agricultural production by raising energy costs along with the increased prices of essential intermediate inputs such as fertilizer, seeds and chemicals (Meng, 2015;Murray and Rivers, 2015;Hasegawa et al, 2016;Mardones and Lipski, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some international studies have found that carbon abatement policies (e.g. carbon tax) led to the decreases in agricultural productions and consumptions as well as an increase in the price level of agricultural products and worsened farmers' income and welfare (Bourne et al. , 2012; Moberg et al.…”
Section: Introductionmentioning
confidence: 99%